The prognostic effect of tumor volume, reduction ratio, and cumulative doses on external beam radiotherapy with central-shielding method and image-guided adaptive brachytherapy for cervical cancer - Ohtaka, Takeru; Ando, Ken; Oike, Takahiro; Noda, Shin-ei; Kaminuma, Takuya; Murata, Kazutoshi; Ohno, Tatsuya (Frontiers in Oncology, 2024)
Objective To evaluate the prognostic effect of tumor volume at diagnosis, tumor reduction ratio during external beam radiotherapy (EBRT) with central-shielding method, and cumulative minimal dose to 90% of the high-risk clinical target volume (CTVHR D90) on combined EBRT and image-guided adaptive brachytherapy (IGABT) for cervical cancer. Methods Consecutive patients who underwent definitive radiotherapy or concurrent chemoradiotherapy for cervical cancer at Gunma University Hospital between January 2010 and December 2019 were retrospectively reviewed. Tumor volume at diagnosis and reduction ratio were calculated using magnetic resonance imaging at diagnosis and before the first IGABT session. The cumulative dose of EBRT and IGABT was calculated as an equivalent dose in 2 Gy fractions (EQD2). Optimal cutoff values were determined according to a receiver operating characteristic curve. Treatment outcomes were evaluated using the Kaplan–Meier method and compared using the log-rank test and Cox proportional hazards regression. Results A total of 254 patients were included in the analysis. The median follow-up for all patients was 57 (2–134) months. The 5-year overall survival (OS) was 81.9%, progression-free survival (PFS) was 71.3%, and local control (LC) was 94.5%. The patients were divided into four groups according to tumor volume at diagnosis and reduction ratio. The group with tumor volume at diagnosis ≥ 34.1 cm3 and reduction ratio < 68.8% showed significantly worse OS, PFS, and LC than the other three groups (All p < 0.05). In this group, the patients with a cumulative CTVHR D90 < 69.6 GyEQD2 showed significantly worse PFS and LC (p = 0.042 and p = 0.027, respectively). In the multivariate analysis of OS, adenocarcinoma/adenosquamous carcinoma, International Federation of Gynecology and Obstetrics 2009 stage III/IV, and a reduction ratio of < 68.8% were independent significant poor prognostic factors (p = 0.045, p = 0.009 and p = 0.001, respectively). In the univariate analysis of LC, a reduction ratio of < 68.8% was the only poor prognostic factor (p = 0.041). Conclusion The patients with large and poorly responding tumors had significantly worse prognoses in terms of OS, PFS, and LC, suggesting that dose escalation should be considered for such tumors.